2016
DOI: 10.1051/0004-6361/201527731
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic flux concentrations from turbulent stratified convection

Abstract: Context. The formation of magnetic flux concentrations within the solar convection zone leading to sunspot formation is unexplained. Aims. We study the self-organization of initially uniform sub-equipartition magnetic fields by highly stratified turbulent convection. Methods. We perform simulations of magnetoconvection in Cartesian domains representing the uppermost 8.5−24 Mm of the solar convection zone with the horizontal size of the domain varying between 34 and 96 Mm. The density contrast in the 24 Mm deep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…Although a modest resolution of 288 grid points was used, each scale height is covered by more than 40 grid points. This differs from the case of convection where the density (and pressure) scale height varies strongly as a function of depth and imposes much more restrictive constraints on the grid size (see, e.g., Käpylä et al 2016).…”
Section: Anisotropy Of Turbulencementioning
confidence: 99%
“…Although a modest resolution of 288 grid points was used, each scale height is covered by more than 40 grid points. This differs from the case of convection where the density (and pressure) scale height varies strongly as a function of depth and imposes much more restrictive constraints on the grid size (see, e.g., Käpylä et al 2016).…”
Section: Anisotropy Of Turbulencementioning
confidence: 99%
“…Leaving the flux emergence out, Kitiashvili et al (2010) showed that uniformly distributed field can be intensified and form a flux concentration corresponding to a pore. A series of works by Warnecke et al (2013Warnecke et al ( , 2016, Brandenburg et al (2013), and Käpylä et al (2016) investigated the intensification of pre-imposed weak field by Negative Effective Magnetic Pressure Instability (NEMPI, Brandenburg et al 2011) in more idealized models. It is very likely that the effects found in this models are also present in more complex realistic simulations.…”
Section: On the Formation Of Sunspotsmentioning
confidence: 99%
“…1 of Käpylä et al 2013). Another possibility would be to apply the so-called reduced sound speed method where the sound speed is artificially changed so that the Mach number does not become too small at the base of the convection zone (Hotta et al 2012;Käpylä et al 2016b).…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%